SISTEM PENDUKUNG KEPUTUSAN EVALUASI HASIL BELAJAR SISWA DI SMK PGRI 3 SIDOARJO MENGGUNAKAN METODE FUZZY AHP (ANALYTICAL HIERARCHY PROCESS) - Ahmad Husain Abiyyu; Lilis Widayanti (Universitas Methodist Indonesia, 2023)
Evaluation of student learning outcomes have an important role for teachers in knowing students abilities and in determining how to guide students. However, in its application to vocational high school PGRI 3 Sidoarjo, the teachers have difficulty regarding the assessment system to evaluate students learning outcomes, the difficulty is in the ranking process. Vocational high school 3 Sidoarjo still used the old and manual systems so the result is that the time needed is inefficient time and made the teachers difficult in processing data. The decision support system of students learning result evaluation at vocational high school 3 Sidoarjo using AHP fuzzy method. The goal is to facilitate the teacher in the student ranking process. The process in this system is the admin inputing students data, classes and scores after that the admin determines the value of each criterion and sub-criterion, then the ranking process is based on class. This decision support system's output is the ranking of students' classes. Using the test results from 20 students, the old system and the new system will be compared. As the result, based on 20 students score data, there were incompatible data, the amount of data were 4 data, with a system accuracy rate of 80%. Unsuitable data due to the old system using 2 criterion while the new system using 5 criterion in ranking.